CLINICAL PRACTICE GUIDELINES ON FALL PREVENTION IN OLDER ADULTS: A NARRATIVE REVIEW (The Research of Medical Science Review, 2025)
Falls among older adults present a significant global health challenge, particularly in regions like Rahim Yar Khan, Pakistan, where healthcare infrastructure limitations and socioeconomic disparities amplify risks. Globally, 28-35% of individuals aged 65 and older experience falls annually, with 10-20% resulting in severe injuries such as fractures or traumatic brain injuries (WHO, 2023). In Pakistan, cultural practices (e.g., indoor footwear use), widespread vitamin D deficiency (72% prevalence among women over 60), and insufficient rehabilitation services further exacerbate these risks (Chee, 2025). In order to suggest context-specific approaches to fall prevention, this narrative study combines global clinical guidelines with local data. Interventions supported by evidence, such as Otago and Tai Chi-style structured exercise programs and non-slip flooring installed in the home, are highly effective. But there are problems with implementing it in Rahim Yar Khan, like a lack of physiotherapists (2.4 PTs per 100,000 people) and a cultural reluctance to assistive equipment (Punjab Healthcare Commission, 2024). According to the Al-Falah Trust (2024), there is potential for innovative local solutions to increase accessibility and adherence, such as community-based exercise programs in mosques and screenings conducted by Lady Health Workers. The review stresses the need of tele-rehabilitation programs and culturally relevant education in preventing falls, and the critical need for policy changes to accomplish this (Sheikh Zayed Medical College, 2025). This review gives Pakistan's ageing population a way to lower the number of fall-related illnesses and improve their quality of life by bringing together global data with regional reality.